2014
DOI: 10.1152/ajplung.00368.2013
|View full text |Cite
|
Sign up to set email alerts
|

EGFR activation suppresses respiratory virus-induced IRF1-dependent CXCL10 production

Abstract: Airway epithelial cells are the primary cell type involved in respiratory viral infection. Upon infection, airway epithelium plays a critical role in host defense against viral infection by contributing to innate and adaptive immune responses. Influenza A virus, rhinovirus, and respiratory syncytial virus (RSV) represent a broad range of human viral pathogens that cause viral pneumonia and induce exacerbations of asthma and chronic obstructive pulmonary disease. These respiratory viruses induce airway epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 61 publications
5
71
1
Order By: Relevance
“…These pathways regulate cell cycling and proliferation, and therefore control the availability of cellular resources for replicating viral genomes. However, each of these host pathways also has critical effects on innate and adaptive immunity (Tang, Amagai et al 1993; Takaoka, Hayakawa et al 2003; Munoz-Fontela, Macip et al 2008; Youlyouz-Marfak, Gachard et al 2008; Zaheer, Koetzler et al 2009; Moore and Chang 2010; Lupberger, Duong et al 2013; Mayumi, Watanabe et al 2013; Kalinowski, Ueki et al 2014; Lulli, Carbone et al 2016; Miciak and Bunz 2016; Zheng, Stamminger et al 2016). It is possible that the immune effects of these oncogenic pathways may be more important in the context of productive virus infections than simply making nucleotides and enzymes available for replicating genomes.…”
Section: Summary and Additional Questionsmentioning
confidence: 99%
“…These pathways regulate cell cycling and proliferation, and therefore control the availability of cellular resources for replicating viral genomes. However, each of these host pathways also has critical effects on innate and adaptive immunity (Tang, Amagai et al 1993; Takaoka, Hayakawa et al 2003; Munoz-Fontela, Macip et al 2008; Youlyouz-Marfak, Gachard et al 2008; Zaheer, Koetzler et al 2009; Moore and Chang 2010; Lupberger, Duong et al 2013; Mayumi, Watanabe et al 2013; Kalinowski, Ueki et al 2014; Lulli, Carbone et al 2016; Miciak and Bunz 2016; Zheng, Stamminger et al 2016). It is possible that the immune effects of these oncogenic pathways may be more important in the context of productive virus infections than simply making nucleotides and enzymes available for replicating genomes.…”
Section: Summary and Additional Questionsmentioning
confidence: 99%
“…Not only are ErbB family members regularly endocytosed during their normal life cycle, but pathogen-ErbB ligation [9,10] and ErbB receptor signalling cascades [11][12][13][14] can contribute to cellular entry of a diverse range of microbes. Pathogen-mediated hijacking of ErbB signalling pathways also results in prolonged host cell survival [11,12,[15][16][17] as well as altered immune responses [18][19][20][21][22][23][24][25][26], which may, in turn, enhance pathogen persistence. Crucially, Trends A wide and diverse variety of microbes have each evolved distinct mechanisms to exploit ErbB receptors, highlighting this receptor kinase family as a critical factor in initiation and maintenance of pathogen infections.…”
Section: Erbb Receptors a Gatekeeper Of Infectious Diseasementioning
confidence: 99%
“…IAV and Rhinovirus (RV)-16 are both capable of inhibiting interferon (IFN)-l production, a critical antiviral cytokine of the airways, through an EGFR-dependent mechanism that results in enhanced viral titres [18]. Suppression of CXCL10 (IFN-g-induced protein 10 (IP-10)), a monocyte and T cell chemokine, has also been shown following IAV, RV, or RSV infection, through virus-induced EGFR signalling [19]. Additionally, NF-kB, a primary transcription factor governing immune responses, is targeted during Klebsiella pneumoniae infection of bronchial epithelial cells [65].…”
Section: Pathogen-induced Modulation Of Immune Responses Via Egfrmentioning
confidence: 99%
“…For example, does bronchoconstriction impair the innate immune responses of airway epithelial cells? Recent studies have shown that EGFR activation induced by viral infection suppresses the production of interferon-and CXCL-10, both of which have antiviral functions in the airway epithelium (45,113). These studies raise the question of whether bronchoconstriction impairs host defense mechanisms against viral infections through the induction of EGFR in patients with asthma.…”
Section: Alteration Of Innate Immunitymentioning
confidence: 99%